Comparison of eggs, larvae, and pupae of plutella xylostella (lepidoptera: Plutellidae) as prey for podisus nigrispinus (Hemiptera: Pentatomidae) - Vacari, Alessandra M. [UNESP]; Bortoli, Sergio A. de [UNESP]; Goulart, Roberto M. [UNESP]; Volpe, Haroldo X. L. [UNESP]; Otuka, Alessandra K. [UNESP]; Veiga, Ana C. P. [UNESP] (Oxford University Press (OUP), 2013)
Understanding the predation on pest insects through controlled feeding on their prey can provide insight into natural methods of pest control. The growth, survival, and development of the predatory stink bug (Podisus nigrispinus Dallas) fed on the eggs, larvae, and pupae of the diamondback moth, Plutella xylostella L, was examined in the laboratory. Second instar P. nigrispinus (12-24 h old) were fed various prey and monitored daily as they molted through nymphal stages and adulthood until death. The growth, survival, and egg production of stink bugs fed P. xylostella larvae and pupae were compared. P. xylostella eggs and first instars are inadequate food sources, whereas fourth instars and pupae can sustain the development of P. nigrispinus. Egg output of females was greater with pupae than with larvae. Male longevity was greater with larvae than with pupae. More P. xylostella larvae than pupae were consumed by P. nigrispinus. The high consumption rates of P. xylostella by P. nigrispinus in the laboratory indicate that this predatory stink bug may be a potential biological control agent for this pest. © 2013 Entomological Society of America.
Keywords: Asopinae; biological control; Brassicaceae; insect biology; predatory stink bug; dicotyledon; egg; egg production; growth rate; larva; longevity; moth; pest control; pest species; potential biocontrol agent; predation; prey availability; pupa; survival